ANALISIS METODOLOGI IJTIHAD INTIQA’I DAN INSYA’I SYEKH YUSUF AL-QARDHAWI TERHADAP FENOMENA BANK ASI - Indra Kusdiana; Muhith; Heri Iswandi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines Yusuf al-Qardhawi’s methodology of intiqa’i and insya’i ijtihad in relation to the phenomenon of human milk banks. This issue is significant because human milk banks provide medical benefits for premature infants, low-birth-weight infants, and babies who cannot receive breast milk from their biological mothers. However, in Islamic law, human milk banks raise several jurisprudential issues related to radha’ah, milk kinship, lineage protection, donor documentation, and legal certainty in Islamic family law. This study uses a qualitative library research method with approaches from usul al-fiqh, maqasid al-shariah, intellectual biography, and document analysis. The findings show that al-Qardhawi’s intiqa’i ijtihad is relevant for selecting earlier juristic opinions that are stronger, more beneficial, and more suitable for modern contexts. Meanwhile, insya’i ijtihad is relevant for formulating new legal reasoning on human milk banks as a modern medical phenomenon that did not exist in the same institutional form in classical Islamic jurisprudence. From the perspective of maqasid al-shariah, human milk banks may support hifz al-nafs by protecting infant survival and health, but they must also preserve hifz al-nasl through proper documentation of milk kinship. This study concludes that human milk banks can be accepted when managed safely, transparently, non exploitatively, and in accordance with Islamic legal principles. Al-Qardhawi’s thought offers a middle path between absolute rejection and unrestricted acceptance of human milk banks.